2011
DOI: 10.1038/ncomms1235
|View full text |Cite|
|
Sign up to set email alerts
|

Larger mitochondrial DNA than Y-chromosome differences between matrilocal and patrilocal groups from Sumatra

Abstract: Genetic differences between human populations are typically larger for the Y-chromosome than for mitochondrial DNA (mtDNA), which has been attributed to the ubiquity of patrilocality across human cultures. However, this claim has been disputed, and previous analyses of matrilocal groups give conflicting results. Here we analyse mtDNA variation (complete mtDNA genome sequences via next-generation sequencing) and non-recombining regions of the Y-chromosome variation (Y-single-nucleotide-polymorphisms and Y-short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 49 publications
4
52
2
Order By: Relevance
“…Haplogroup R12 shares with R21 three mutations at sNPS 10,398, 11,404, and 16,295 as shown in Phylotree build17 [36]. As R21 was found first in Malaysian Negrito groups [15, 118, 119], later in Sumatra [120] and in Dayak from Borneo [121], its shared root would point to a possible common ancestor somewhere in Southeast Asia which is congruent with a western, a note of caution to this hypothesis is necessary because a Burman R* sequence (KP346030) found in Myanmar [19], shares with R21 also three mutations at NPS 1709, 1719, and 15,613. Counting homoplasies and reversions in phylotree build 17 for each trio of mutations, we obtained a total of 45 independent events for the R12/R21 root and a total of 44 for the R21/R* alternative.…”
Section: Resultsmentioning
confidence: 99%
“…Haplogroup R12 shares with R21 three mutations at sNPS 10,398, 11,404, and 16,295 as shown in Phylotree build17 [36]. As R21 was found first in Malaysian Negrito groups [15, 118, 119], later in Sumatra [120] and in Dayak from Borneo [121], its shared root would point to a possible common ancestor somewhere in Southeast Asia which is congruent with a western, a note of caution to this hypothesis is necessary because a Burman R* sequence (KP346030) found in Myanmar [19], shares with R21 also three mutations at NPS 1709, 1719, and 15,613. Counting homoplasies and reversions in phylotree build 17 for each trio of mutations, we obtained a total of 45 independent events for the R12/R21 root and a total of 44 for the R21/R* alternative.…”
Section: Resultsmentioning
confidence: 99%
“…For example, although we have no reason to expect a bias toward specific groupings of populations, by limiting our mitochondrial analysis to the HVS1 region, we might have missed distinctions in mitochondrial haplotype variation across villages that would have been apparent had we analyzed complete mtDNA sequences (Gunnarsdottir et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…To determine the phylogenetic positions of the newly discovered Cambodian haplogroups, we employed ARTICLE 133 complete mtDNA genome sequences (including the 98 newly sequenced mitogenomes in the present study and the 35 previously reported mitogenomes from Asia 14,17,[22][23][24][25][28][29][30]32,42,43,48,52 ) to construct the phylogenetic tree. From the NCBI nucleotide database (http://www.ncbi.nlm.nih.gov), we selected 35 mitogenomes, including 10 reported but unclassified mitogenomes related with the newly defined haplogroups in Cambodians.…”
Section: Methodsmentioning
confidence: 99%
“…22), which belong to a M78 sub-branch deeply divergent from the four Cambodian samples of the Stieng ethnic group. The haplogroup M69 is defined by a short mutation motif C4392T-T11365C, which is shared by a sequence (HM596653) from Sumatra (Indonesia) 23 , but with a deep divergence with the twelve sequences from four different Cambodian ethnic groups. The haplogroup M59 is defined by a long motif of A249G-G9380A-T10256C-C11140T-G14040A-T16140C-C16278T, shared by a sequence (JQ702247) from Singapore 24 but with a deep divergence from a Cambodian sample of the Tompoun ethnic group.…”
Section: Classification Of the Cambodian Mtdna Haplogroupsmentioning
confidence: 99%